A fluoride ion-mediated continuous etching–redeposition strategy to synthesize Si nanocomposites with appropriate SiO2 coating layers for Li-ion batteries. Issue 88 (3rd October 2018) - Fan, Xiaoming; Zhao, Junhao; Yang, Zeheng; Zhang, Weixin
Abstract : A silicon core in a silica shell: an etching–redeposition strategy to synthesize silicon nanocomposites with high rate capability and cycling stability in LIBs. Abstract : Silicon nanocomposites with surface coating have been promising candidates for high-performance anodes in Li-ion batteries. Here we report a simple yet effective way to synthesize Si@SiO2 nanocomposites with amorphous SiO2 coating through a fluoride ion-mediated continuous etching–redeposition process. The Si@SiO2 nanocomposite anode exhibits significantly improved lithium storage properties, with a reversible capacity of 1356 mA h g −1 at 2.1 A g −1 for 300 cycles.